While self studying analytic number theory from Tom M Apostol introduction to analytic number theory I have following doubt in section 14.10 .

I am adding it's image highlighting the part in which I have doubt.

enter image description here

My doubt is - how $ \sum_{m=1}^{\infty} G'_A (x^m) x^m $ = $\sum_{m=1}^{\infty} \sum_{n\epsilon A} f(n) x^{mn} $ .

I think there should be a additional term $x^{mn+m} $ on RHS as x × $G'_A(x) = \sum_{n \epsilon A} f(n) x^n $ and then I have to put x = $x^m $ and then multiply by $x^m $ .

Can somebody please explain where I had made a mistake.

  • 1
    $\begingroup$ "how is $G'_A (x^m) x^m = \sum_{m=1}^{\infty} \sum_{n\epsilon A} f(n) x^{mn} $". It isn't. It's $\sum_{m=1}^\infty G'_A (x^m) x^m = \sum_{m=1}^{\infty} \sum_{n\epsilon A} f(n) x^{mn} $. $\endgroup$ – Angina Seng Jan 7 '20 at 4:57
  • $\begingroup$ @Lord Shark the Unknown yes that was a mistake, I have edited it. $\endgroup$ – Ben Jan 7 '20 at 5:12

Using your expression, i.e., where you multiplied both sides of the expression for $G'_A(x)$ by $x$, you could replace all $x$ with $x^m$ to get

$$\begin{equation}\begin{aligned} x\left(G'_A(x)\right) & = \sum_{n \epsilon A} f(n) x^n \\ x^m\left(G'_A(x^m)\right) & = \sum_{n \epsilon A} f(n) \left(x^m\right)^n \\ G'_A(x^m)x^m & = \sum_{n \epsilon A} f(n) x^{mn} \end{aligned}\end{equation}\tag{1}\label{eq1A}$$

Alternatively, you could do the substitution first and then the multiplication, with this, showing it in detail, resulting in

$$\begin{equation}\begin{aligned} G_A(x) & = \sum_{n\epsilon A} \frac{f(n)}{n} x^{n} \\ G'_A(x) & = \sum_{n\epsilon A} f(n) x^{n-1} \\ G'_A(x^m) & = \sum_{n\epsilon A} f(n) \left(x^m\right)^{n-1} \\ G'_A(x^m) & = \sum_{n\epsilon A} f(n) x^{mn - m} \\ G'_A(x^m)x^m & = \sum_{n\epsilon A} f(n) x^{mn - m}x^m \\ G'_A(x^m)x^m & = \sum_{n\epsilon A} f(n) x^{mn} \end{aligned}\end{equation}\tag{2}\label{eq2A}$$

In either case, taking the sum from $m = 1$ to $\infty$ of both sides gives the part you're asking about, i.e,.

$$\sum_{m=1}^{\infty} G'_A(x^m)x^m = \sum_{m=1}^{\infty} \sum_{n\epsilon A} f(n) x^{mn} \tag{3}\label{eq3A}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.